2015
DOI: 10.1128/jvi.01415-15
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nectin-1 and Herpesvirus Entry Mediator as Cellular Receptors for Herpes Simplex Virus 1 on Primary Murine Dermal Fibroblasts

Abstract: The cellular proteins nectin-1 and herpesvirus entry mediator (HVEM) can both mediate the entry of herpes simplex virus 1 (HSV-1). We have recently shown how these receptors contribute to infection of skin by investigating HSV-1 entry into murine epidermis. Ex vivo infection studies reveal nectin-1 as the primary receptor in epidermis, whereas HVEM has a more limited role. Although the epidermis represents the outermost layer of skin, the contribution of nectin-1 and HVEM in the underlying dermis is still open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 44 publications
8
40
0
Order By: Relevance
“…Moreover, this is also the scenario in HeLa cells where there is 60-fold less nectin-1 mRNA present, suggesting that even low levels of nectin-1 can support HSV-1 entry. Together with our results on HeLa and nTERT cells presented here, nectin-1 has now been shown to be the preferred entry receptor over HVEM in a range of different cell types (37)(38)(39)(40)(41). As such, it could be argued that the relatively high level of nectin-1 expression in nTERT cells explains the rapid entry phenotype.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, this is also the scenario in HeLa cells where there is 60-fold less nectin-1 mRNA present, suggesting that even low levels of nectin-1 can support HSV-1 entry. Together with our results on HeLa and nTERT cells presented here, nectin-1 has now been shown to be the preferred entry receptor over HVEM in a range of different cell types (37)(38)(39)(40)(41). As such, it could be argued that the relatively high level of nectin-1 expression in nTERT cells explains the rapid entry phenotype.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, these expression levels do not appear to correlate with their effectiveness as receptors. Despite its low level on fibroblasts, our results support nectin-1 as the major mediator of HSV-1 entry into both cell types of murine skin [3,4]. In the absence of nectin-1, HVEM can replace it as a receptor, and appears to do so more efficiently in fibroblasts than in keratinocytes.…”
supporting
confidence: 64%
“…Whether both internalization pathways lead to productive infection is difficult to determine although studies in human keratinocytes support endocytic uptake as contributing to HSV-1 entry [7]. In addition, we demonstrated that entry into skin cells is cholesterol-and dynamin-mediated [4,7]. Based on the known functions of dynamin, the finding that inhibition of dynamin GTPase activity results in a Editorial…”
Section: +mentioning
confidence: 83%
See 2 more Smart Citations